POLITIK HUKUM ITSBAT NIKAH - Rahayu, Ninik (Musawa Jurnal Studi Gender dan Islam, 2013)
Marital Itsbat is still necessary as a policy, even for marriages conducted prior to the  entry to force of Law No. 1 of 1974 on Marriage. Changes regarding the provision of Itsbat are necessary to ensure that the law could still act as the guardian of legal certainty to achieve justice for citizens. In reality, a policy of legitimizing marital. Itsbat is necessary in Indonesia’s legal politics, which is not only based on past marital laws (iusconstituendum), current laws but must also encompass the need to regulate future marriages (iusconstitutum. Considering thse needs, the policy in question must not only fulfill the needs of Muslims, but also those who are deprived  of the chance to legitimize their marriages’ documentation; whether due to poverty, ignorance or other factors (such as the religious validity of the couple), migration or other issues. This material change of Itsbat should still be based on the principle of protection and non-discrimination towards women so that it can still give a sense of justice to women. In other words, it should not only stem from the fulfillment of the requirements in Law No. 1 of 1974, which in reality has been proven to be discriminatory to women.